The lieutenant don't know one Marine's story of warfare and combat logistics in Afghanistan - Clement, Jeffrey D. (Casemate Publishers, 2014)
In our wars since 2001, the term "front line" has long since lost its meaning. Our opponents have not been able to stand against conventional forces in battle and instead have resorted largely to guerrilla tactics, engaging our forces with IEDs, snipers, and ambushes. Into the mix of behind-the-lines attacks, combat logistics have played a larger role than ever.